First International University Course of Specialization in Lifestyle Medicine: Primer Curso Internacional de Especialización en Medicina del Estilo de Vida - De La Cruz Vargas, Jhony A. (2021)
The Closing Ceremony and Awarding of Diplomas of the First International Course of Specialization in  Lifestyle  Medicine:  Lifestyle  Medicine  Fundamentals,  with  a  Focus  on  Primary  Health  Care,  organized by the Chair of Lifestyle Medicine of the Universidad Ricardo Palma in collaboration with the Latin American Lifestyle Medicine Association, was held with great satisfaction.